Validez y confiabilidad de la escala rasgo de metaconocimiento emocional (TMMS-24) en profesores universitarios (2019)
Some studies support the conception of emotional intelligence - EI as a predictor of work performance, they are also useful in the selection process of the best candidate for organizations. That is, people with a high level of EI are more likely to be successful in the professional field, being more adaptable to stressful life events, using appropriate coping strategies, in addition to the ability they develop for teamwork. The objective of this study was to examine the reliability and validity of trait meta mood scale, in a sample of university professors from private institutions of higher education, in order to contribute to the knowledge about its viability in the evaluation of inter and intrapersonal emotional intelligence levels of this population. The study involved 235 university professors with a minimum experience of two years and linked to a private higher education institution in the city of Bucaramanga. The process included the validation of content through the criterion of judges, pilot test, measurement of the reliability of the test by internal consistency and the determination of construct validity, through factor analysis. The results indicate that the factorial structure of the TMMS-24 Scale in the evaluated sample is made up of the three dimensions defined in the Spanish version and that the scale reduced to 20 items constitutes an instrument with adequate values of validity and reliability in the measurement of Emotional intelligence in university professors. In conclusion, it is considered that this scale constitutes a useful instrument for measuring and researching the emotional intelligence construct as an important organizational variable to improve the quality of working life of workers and the organizational dynamics of higher education institutions. It is suggested to conduct studies in other regions of the country in order to strengthen the generalization of the results.